Ergonomics workstation for home office / Norafiza Mohd Hardi, Norhafiza Hashim and Hasyimah Razali - Mohd Hardi, Norafiza; Hashim, Norhafiza; Razali, Hasyimah (Faculty of Business and Management, Universiti Teknologi MARA Cawangan Kedah, 2022)
During the COVID-19 outbreak caused by the novel coronavirus, working from home became the new way of working. The pandemic has changed the way we work and transformed the workplace culture with more people working remotely. A survey conducted by human resources solutions agency, Randstad released the result of their H1 2021 Workmonitor survey in Malaysia found that 69% of Malaysians want to continue to work from home until the COVID-19 vaccine has been widely distributed (Randstad, 2021).